Hexagonal boron nitride nanosheet/carbon nanocomposite as a high-performance cathode material towards aqueous asymmetric supercapacitors. Issue 4 (March 2019) - Li, Tianli; Jiao, Xiuyan; You, Ting; Dai, Fang; Zhang, Panpan; Yu, Feng; Hu, Lu; Ding, Liwen; Zhang, Lei; Wen, Zubiao; Wu, Yuping
Abstract: The two-dimensional hexagonal boron nitride ( h -BN) has garnered tremendous interest due to its unique mechanical, thermal and electronic properties. However, the application of h -BN has been restricted as electrode materials for supercapacitors because of its wide band gap and rather low conductivity. Herein, a carbon-modified hexagonal boron nitride nanosheet ( h -BN/C) nanocomposite is prepared through a facile and scalable solid-state reaction. Interestingly, the h -BN/C nanocomposite as cathode material exhibits a pair of distinct and reversible redox peaks in 2 M KOH aqueous electrolyte. Because of the enhanced electrical conductivity derived from the modified carbon and the increased specific surface area, the h -BN/C nanocomposite presents a high specific capacitance of 250 F g −1 at the current density of 0.5 A g −1 . More importantly, the fabricated aqueous asymmetric supercapacitor with the h -BN/C as cathode and activated carbon as anode displays an operating voltage of 1.45 V, an energy density of 17 Wh kg −1 at a power density of 245 W kg −1, and high stability up to 1000 cycles. Therefore, h -BN/C nanocomposite would promisingly be a cathode material for aqueous asymmetric supercapacitors.